2019
DOI: 10.1111/jgs.15996
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Hospital Transfers Using INTERACT Acute Care Transfer Tools: Lessons from MOQI

Abstract: OBJECTIVES We explored the differences in potentially avoidable/unavoidable hospital transfers in a retrospective analysis of Interventions to Reduce Acute Care Transfers (INTERACT) Acute Transfer Tools (ACTs) completed by advanced practice registered nurses (APRNs) working in the Missouri Quality Improvement (QI) Initiative (MOQI). DESIGN Cross‐sectional descriptive study of 3996 ACTs for 32.5 calendar months from 2014 to 2016. Univariate analyses examined differences between potentially avoidable vs unavoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Reduced healthcare costs were mentioned in 9 of 136 occurrences of facilitator themes, or 6.62% [ 7 , 8 , 9 , 12 , 14 , 23 , 30 ]. Unrestrictive or least restrictive scope of practice for NPs was mentioned in 10 of 136 occurrences of facilitator themes, 7.35% [ 10 , 14 , 16 , 17 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced healthcare costs were mentioned in 9 of 136 occurrences of facilitator themes, or 6.62% [ 7 , 8 , 9 , 12 , 14 , 23 , 30 ]. Unrestrictive or least restrictive scope of practice for NPs was mentioned in 10 of 136 occurrences of facilitator themes, 7.35% [ 10 , 14 , 16 , 17 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The negative barrier theme most often mentioned was the restrictive scope of practice for NPs, identified in 13 of 45 occurrences (28.89%) reviewed [ 9 , 14 , 16 , 20 , 23 , 24 , 31 , 32 , 34 , 35 , 36 ]. Lack of policy and funding, Medicare regulations, state regulatory constraints, prohibited billing for visits, and no authority to write or change orders were all contributors to restrictive scope of practice for NPs [ 9 , 23 , 24 , 32 , 34 , 35 ]. These restrictions required direct or indirect supervision from physicians for NPs, as well [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent staff education and role modeling help overcome common nursing staff reactions to resident illness and change in condition. For instance, staff reactions to a resident change in condition is often "ship to hospital"; however, more complete assessment often reveals actions that are more appropriate to manage the clinical situation and treat the resident in place at the NH (9,20). Another recommendation is for nursing home leadership to invest in staff with the clinical skills (RNs and an APRN) to role model how to detect changes in health status early, how to do more complete assessments, communicate information to healthcare providers clearly, and guide implementing clinical interventions that help residents recover quickly within the nursing home.…”
Section: Discussionmentioning
confidence: 99%
“…Another recommendation is for nursing home leadership to invest in staff with the clinical skills (RNs and an APRN) to role model how to detect changes in health status early, how to do more complete assessments, communicate information to healthcare providers clearly, and guide implementing clinical interventions that help residents recover quickly within the nursing home. We have found that most diagnostic workups can be completed readily within the nursing home so that the majority of changes in health status can be managed without hospitalization (9,20).…”
Section: Discussionmentioning
confidence: 99%
“…As part of the MOQI project, APRNs documented retrospective details about every resident’s hospital transfer into an adapted INTERACT acute care transfer (ACT) tool using Qualtrics survey software [ 21 , 22 ]. The ACT tool contains open- and closed-ended questions about each acute care transfer.…”
Section: Methodsmentioning
confidence: 99%